An Experimental Approach for Piezoelectric Sensor based Wireless Battery Charger - prasad Tripathy, Hara; Pattanaik, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2025)
According to the modern era the energy consumed by the human is in huge amount and it is increasing day by day as per the requirement, the modernisation in the society results the continuous increment of the energy. However, this results in exhausting and wastage of energy. This work is proposed for the proper consumption of the human locomotary energy which are wasted by the humans. The energy produced by the walking, running and jumping is very much relevant and important to the highly populated countries. This work demonstrates the construction and the implementation of energy collecting system with the conversion of energy by the human movement to operational form. This work describes the technique for the charging the electronic gadgets by producing said electrical voltage through said array by means of piezoelectric sensors mounted on the sole of the footwear